PENDIDIKAN AGAMA ISLAM UNTUK MEMPROMOSIKAN PERDAMAIAN DALAM MASYARAKAT PLURAL - Baidhawy, Zakiyuddin (Analisis: Jurnal Studi Keislaman, 2014)
RELIGIOUS EDUCATION IN PROMOTING THE PEACE AMONG PLURAL SOCIETIES: Political and ideological tensions often led to hatred speeches and messages of intolerance against ethnic other  groups, cultures, and religions. Religious Education can play a role in promoting a positive view of diversity.  This study provides a review of the curriculum of Islamic studies (PAI) that  exist in four junior high schools in Solo, as well as the perceptions of teachers and students about religious diversity. This study adopted a qualitative approach, using content analysis of written documents such as student’s manuals and teacher handbooks), combined with a semi- structured  questionnaire for principals, teachers, and students, and Focused Group Discussion to assess their perceptions and attitudes  towards  diversity  and difference.  This  study  found that the curriculum of PAI lacked content aimed at instilling co- existence and peace education. Also, about a third of teachers and students  reported intolerance towards different religions. The result is then followed by a pilot project to  develop an Islamic-based  Peace Education, which aims to build a peace- loving character among young people, through teaching mutual respect, non-violence, social justice and co-existence, using the values of Islam.